Antagonism and antibiotic resistance drive a species-specific plant microbiota differentiation in Echinacea spp. Issue 8 (14th June 2018) - Maggini, Valentina; Miceli, Elisangela; Fagorzi, Camilla; Maida, Isabel; Fondi, Marco; Perrin, Elena; Mengoni, Alessio; Bogani, Patrizia; Chiellini, Carolina; Mocali, Stefano; Fabiani, Arturo; Decorosi, Francesca; et al.
ABSTRACT: A key factor in the study of plant-microbes interactions is the composition of plant microbiota, but little is known about the factors determining its functional and taxonomic organization. Here we investigated the possible forces driving the assemblage of bacterial endophytic and rhizospheric communities, isolated from two congeneric medicinal plants, Echinacea purpurea (L.) Moench and Echinacea angustifolia (DC) Heller, grown in the same soil, by analysing bacterial strains (isolated from three different compartments, i.e. rhizospheric soil, roots and stem/leaves) for phenotypic features such as antibiotic resistance, extracellular enzymatic activity, siderophore and indole 3-acetic acid production, as well as cross-antagonistic activities. Data obtained highlighted that bacteria from different plant compartments were characterized by specific antibiotic resistance phenotypes and antibiotic production, suggesting that the bacterial communities themselves could be responsible for structuring their own communities by the production of antimicrobial molecules selecting bacterial-adaptive phenotypes for plant tissue colonization. Abstract : A deep phenotypic characterization of a collection of cultivable bacterial strains from two plant species suggests that socio-microbiological interactions are the main players in plant-specific differences in the composition of bacterial communities.